The Effects of Demographic Factors on Investment Decision: Financial Literacy and Behavioral Bias as Mediating Variables - Alwina Salim; Ignatius Roni Setyawan (International Journal of Application on Economics and Business, 2023)
In society after COVID-19 Pandemic, awareness on financial well-being is on the rise and many attempts to achieve it through investment. But, to invest means to make decision among numerous alternatives and risks. This research aims to find out how investment actors’ demographic factors, financial literacy, and behavioral bias affect the investment decisions they make, where it highlights upon a point still rarely disclosed: whether financial literacy and behavioral bias are able to mediate the relationship between demographic factors and investment decision. The result for SEM-PLS analysis of 151 young investment actors below the age of 25 and adult investment actors of 25 years old and above shows that behavioral bias can act as a mediator while financial literacy cannot; demographic factors that is addition of family members, financial management behavior of financial literacy, and behavioral bias in the form of overconfidence all have a positive and significant effect as well. These findings give the implication that responsibilities towards one’s family, as well as financial behavior and self-confidence, play a noticeable role on investment decision.